Investigating Students’ Perceptions of Team-Based Projects and TPACK Integration in English Language Learning - Erdiana, Nira; Fajrina, Dian; Fajriani, Ukhti; Yusuf, Yunisrina Qismullah; Dekhnich, Olga V. (Institut Agama Islam Negeri Imam Bonjol Padang, 2025)
This study explores students’ perceptions of team-based project learning integrated with Technological Pedagogical Content Knowledge (TPACK) in an English Teaching Methodology class at Syiah Kuala University. The research framework, adapted from Kemendikbud, focuses on six key stages: questioning, designing, scheduling, monitoring, assessing, and evaluating. Data were gathered from 30 students through a structured questionnaire and analyzed quantitatively, using percentage and interval ranges to determine perceptions. The results show that students held overwhelmingly positive views of team-based projects, with mean scores consistently falling in the ‘Agree’ to ‘Strongly Agree’ categories. Students valued the collaborative nature of the projects, which helped them develop critical skills such as critical thinking, creativity, and time management. The integration of TPACK further enriched their learning experience by facilitating meaningful application of technology in teaching. These findings suggest that team-based projects, when integrated with TPACK and guided by a structured framework, can significantly improve learning outcomes in English language education. Future research should investigate the long-term impacts of these approaches and address potential implementation challenges to enhance their effectiveness.